THE RELATIONSHIP OF FAMILY KNOWLEDGE AND SUPPORT WITH PREGNANT WOMEN'S COMPLIANCE WITH PREGNANT WOMEN'S COMPLIANCE WITH IRON TABLETS - Nurhaida; Rambe, Delvia; Rikandi, Meta; Refialdinata, Jeki; Saputri, Melda (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
In an effort to prevent anemia in pregnant women, apart from providing iron tablets and their distribution system, the thing that has the most influence on the success of the iron supplementation program is the compliance of pregnant women in taking Fe tablets obediently according to the recommendations of health workers. The initial survey showed that 4 out of 10 respondents were not compliant in taking iron tablets. This study aims to determine the relationship between knowledge and family support with adherence to consuming iron tablets at the Lubuk Begalung Health Center. This research design is an analytical method, using a cross sectional approach. This research was conducted in the working area of the Lubuk Begalung Health Center in Padang which was carried out from 24 July - August 2023. In this study, pregnant women at the Lubuk Begalung Health Center in 2023, population 503 with 83 respondents. The results showed that most pregnant women (62.7%) had poor knowledge and most (65.1%) had poor family support. Statistical tests concluded that there was a significant relationship between knowledge p0.007 (p <0.05) and family support p0.035 (p <0.05) with compliance of pregnant women taking iron tablets at the Lubuk Begalung Health Center Padang. It is recommended that health services at the Lubuk Begalung Health Center provide counseling regarding knowledge and family support in the compliance of pregnant women in consuming iron tablets.